Etika Komunikasi dalam Naskah Wicara Dora tuwin Wicara Temen tumrap ing dalem Sasrawungan (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2023)
Indonesian citizens have a low level of politeness in their communication, so there is a need to increase the understanding of communication ethics, especially those that come from local wisdom.The purpose of this study is to present inventations, descriptions, transliterations, edits, translations, and ethical analysis of communication in the manuscript Wicara Dora tuwin Wicara Temen tumrap ing dalem Sasrawungan (for further abbreviation WDWTS). The method employed is the analysis of the document using a philology approach and communication with the research object of text and manuscript WDWTS. The result of this research is that only 1 copy of WDWTS manuscript was found, namely PNRI collection with codex number NB 1090, description of manuscript and text, script transfer from Javanese script to Latin script by correcting 6 word writing, editing 2 words with a single script, translation of text from Javanese to Indonesian with 1 translator's note, and knowledge of text content regarding Javanese views on communication ethics, including (1) communication must be correct, which is the real message; (2) communication must be precise, which is message conveyed according to the situation and context; and (3) communication must be helpful, which is message being delivered contains substance. Keywords: Communication ethics; philology; Wicara Dora tuwin Wicara Temen tumrap ing dalem Sasrawungan